2021
DOI: 10.31557/apjcc.2021.6.3.237-241
|View full text |Cite
|
Sign up to set email alerts
|

Role of Computed Tomography in the Evaluation of Pediatric Retroperitoneal Masses: A Retrospective Study

Abstract: Objective: Retroperitoneum is one of the largest spaces in the body. Retroperitoneal (RP) masses are common in paediatric age group and present with vague clinical features. Computed Tomography (CT) is an excellent imaging modality in the evaluation of RP masses. The aim of this study was to evaluate the role of CT in the detection and characterization of RP masses. Materials and Methods: 28 clinically suspected or sonographically detected RP masses formed the material of the study. Detailed clinical history w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In evaluating retroperitoneal masses with a CT scan, a study by Vikrant et al found the diagnostic accuracy of CT scan to be 85.7 %. 6 Factors such as the late presentation of many of our cases, evidenced by the large tumour size at presentation leading to uncertainty in the primary organ of origin, particularly in neuroblastoma and nephroblastoma cases, may have been a limiting factor. In addition, the lack of a standardized protocol for CT studies from other imaging facilities may have contributed to the relatively lower accuracy for those tumours.…”
Section: Rhabdomyosarcomamentioning
confidence: 86%
See 1 more Smart Citation
“…In evaluating retroperitoneal masses with a CT scan, a study by Vikrant et al found the diagnostic accuracy of CT scan to be 85.7 %. 6 Factors such as the late presentation of many of our cases, evidenced by the large tumour size at presentation leading to uncertainty in the primary organ of origin, particularly in neuroblastoma and nephroblastoma cases, may have been a limiting factor. In addition, the lack of a standardized protocol for CT studies from other imaging facilities may have contributed to the relatively lower accuracy for those tumours.…”
Section: Rhabdomyosarcomamentioning
confidence: 86%
“…Fortunately, newer multi-detector CT models boast of lower radiation dose techniques/algorithms and shorter scan times. 6 On the other hand, Magnetic Resonance Imaging provides superb soft tissue resolution and is ideal for evaluating the Central Nervous System. However, it is more expensive and less available; it has long image acquisition times with the need for longer periods of specialized sedation than required for CT scans.…”
Section: Introductionmentioning
confidence: 99%